1966
DOI: 10.1111/j.1151-2916.1966.tb13265.x
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectrics of Ultrafine Particle Size: I, Synthesis of Titanate Powders of Ultrafine Particle Size

Abstract: Two methods used to synthesize high‐purity ferroelectric titanate powders in controlled, narrow size distributions, with average particle diameters <1000 A, were: (1) isothermal pyrolysis of barium titanyl oxalate or mixed calcium‐barium titanyl oxalates as low as 550° and 825°C, respectively, average particle sizes depending strongly on the pyrolysis temperature; and (2) hydrolysis of titanate esters in barium hydroxide. Using solvent media of controlled polarity, high‐purity stoichiometric BaTiO3 was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(53 citation statements)
references
References 2 publications
0
52
0
1
Order By: Relevance
“…Barium titanium oxalate [49] and other barium and titanium compounds have also been used to prepare high-purity BaTiO 3 . Small, uniform powders have been fabricated in an effort to produce more reactive powders [50][51][52].…”
Section: Batio 3 (Bt)mentioning
confidence: 99%
“…Barium titanium oxalate [49] and other barium and titanium compounds have also been used to prepare high-purity BaTiO 3 . Small, uniform powders have been fabricated in an effort to produce more reactive powders [50][51][52].…”
Section: Batio 3 (Bt)mentioning
confidence: 99%
“…Andrich 9 reported that each 120°C 0°C À 90°C cubic 3 tetragonal 3 monoclinic 3 rhombohedral mole% SrTiO 3 added lowered the Curie temperature of BaTiO 3 from 125°C by À3% and each mole% PbTiO 3 added raised the Curie temperature by 5%. Hence (Ba 1Àx Sr x )TiO 3 and (Ba 1Àx Pb x )-TiO 3 can be tailored so that a given positive temperature coefficient device can operate either above or below 125°C (Eqns [1] and [2] The advantages are simplicity and low cost, but the disadvantages are that the high calcining temperature results in very large grain sizes and therefore cannot be used to obtain materials with a high dielectric constant; 10 if we want fine powder, grinding is required, leading to pollution problems; moreover, the mixing of large amounts of starting materials is not easy and can produce mixtures of Ba 2 TiO 4 , Ba 6 Ti 17 O 10 and BaTi 4 O 9 phases as sideproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Among them the hydrolysis of metal alkoxide 1 , oxalate precipitation in ethanol 2 , and alcoholic dehydration of citrate solution 3 are among the more attractive methods. In 1956 Clabaugh et al 4 described the preparation of barium titanyl oxalate tetrahydrate for conversion to high-purity barium titanate.…”
Section: Introductionmentioning
confidence: 99%
“…Several low-temperature chemical routes have been reported for the synthesis of BaTiO 3 -based solid solutions. [5][6][7][8][9][10][11][12][13] In the co-precipitation and hydrothermal methods, stoichiometry deviations and formation of biphasic solid solutions have been reported. Also, the high temperatures Tࢽ500c C required for achieving complete solid solution in some of the low-temperature methods such as sol-gel and MOD make them less favourable.…”
Section: Introductionmentioning
confidence: 99%